Fear conditioning of SCR but not the startle reflex requires conscious discrimination of threat and safety - Sevenster, Dieuwke; Beckers, Tom; Kindt, Merel (Frontiers in Behavioral Neuroscience, 2014)
There is conflicting evidence as to whether awareness is required for conditioning of the skin conductance response (SCR). Recently, Schultz and Helmstetter (2010) reported SCR conditioning in contingency unaware participants by using difficult to discriminate stimuli. These findings are in stark contrast with other observations in human fear conditioning research, showing that SCR predominantly reflects contingency learning. Therefore, we repeated the study by Schultz and Helmstetter and additionally measured conditioning of the startle response, which seems to be less sensitive to declarative knowledge than SCR. While we solely observed SCR conditioning in participants who reported awareness of the contingencies (n = 16) and not in the unaware participants (n = 18), we observed startle conditioning irrespective of awareness. We conclude that SCR but not startle conditioning depends on conscious discriminative fear learning.